2020
DOI: 10.2196/20961
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Partner Relationships and Sexual and Reproductive Health: Cross-Sectional, Online Survey Study

Abstract: Background In the past few months, the coronavirus disease (COVID-19) pandemic has caused extensive economic and social damage. Objective The purpose of this study was to assess the impact of COVID-19–related measures on partner relationships and sexual and reproductive health in China. Methods From May 1 to 5, 2020, 3500 young Chinese individuals were recruited through WeChat or Weibo to participate in a su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
260
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(290 citation statements)
references
References 16 publications
17
260
3
10
Order By: Relevance
“…Several studies have focused on the changes in the frequency of sexual life during the epidemic, [13] , 14 , 15 , 16 , 17 while the present study is firstly reported the relationship with the sexual function of men. The frequency of sexual life was significantly related to changes in erectile function and ejaculatory control ability, and subjects with a low frequency of sexual life had less partner time and less intimacy behavior with sexual partners.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have focused on the changes in the frequency of sexual life during the epidemic, [13] , 14 , 15 , 16 , 17 while the present study is firstly reported the relationship with the sexual function of men. The frequency of sexual life was significantly related to changes in erectile function and ejaculatory control ability, and subjects with a low frequency of sexual life had less partner time and less intimacy behavior with sexual partners.…”
Section: Discussionmentioning
confidence: 85%
“…A few studies have reported decreased frequency of sexual life, decreased sexual satisfaction, and deteriorated partner relationships between sexual partners. [13] , 14 , 15 , 16 , 17 Most studies were focused on women or a mixture of women and men, while the sexual function of men has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In another Italy-based study conducted on reproductive-age women, it was shown that both the FSFI score and the frequency of sexual intercourse decreased during pandemic [ 56 ]. It was found in an online survey study including 3500 individuals that the frequency of sexual intercourse decreased in 41% of the participants, and frequency of masturbation increased in 30% of those [ 57 ]. Lastly, in a recent study from China conducted in the period of COVID-19, it was shown that total sexual satisfaction and frequency ratio decreased, which is in accordance with the current study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The containment had a general impact on the personal lives of all entire population worldwide, especially on their emotional relationships and sexual behavior. COVID-19 also caused disruptions in reproductive health services such as prenatal and postnatal care, childbirth and abortion services, contraception availability, and the management of sexually transmitted infections [ 1 ]. In Europe, there were wide disparities in access to abortion care since the start of COVID-19 pandemic, with reduced access in a number of countries due to government inaction in lifting abortion regulations to enable safe abortion care amid healthcare system disruptions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%